Analisis Strategi Bauran Pemasaran dalam Meningkatkan Volume Penjualan pada Geprek Mania Bungah Gresik - Lidinul Khaq; Sukaris; Nur Cahyadi (Masyarakat Ekonomi Syariah Bogor, 2024)
The problem to be studied in this thesis is: How to analyze the marketing mix strategy implemented at Geprek Mania Bungah Gresik in increasing sales. The purpose of this research is to determine the analysis of the marketing mix strategy implemented at Geprek Mania Bungah Gresik in increasing sales. To answer the above questions, researchers used descriptive research methodology. Research is carried out to analyze circumstances, conditions or other things that have been mentioned, data collection is carried out by means of observation and interviews which are described in the form of a research report. The results of these findings and research show that Geprek Mania Bungah has implemented a marketing mix strategy using the 4P variables, namely: product, price, place and promotion which makes Geprek Mania's sales volume increase, increase the number of consumers and can provide profits for Geprek Mania Bungah.